Leaving The Life: Exploring Services for Women Exiting Prostitution - Cascio, Katherine A. (2017)
Women in prostitution (WIP) are significantly more likely to experience mental health issues and trauma than the general population (Farley, 2003; Ling, Wong, Holroyd, & Gray, 2007; Rössler et al. 2010; Roxburgh, Degenhardt, & Copeland, 2008). Previous research addressing the mental health of WIP emphasizes treating trauma to help women exit, both trauma that predated entry into prostitution and trauma experienced during prostitution (Carter & Dalla, 2006; Farley, 2003). Very little research is available on services for WIP, leaving psychotherapists with limited guidance on providing effective mental health treatment. Although programs exist exclusively to assist women leaving prostitution, little is known about what services they offer or if their services are trauma-informed. Because of this dearth, this study consists of exploratory program evaluations of eight agencies that focus primary on serving WIP to understand what services are provided to this population and how services address trauma. Constructive process evaluations are guided by Program Theory (Chen, 2015) and analysis uses Constructivist Grounded Theory to begin to fill research gaps about what services are available to WIP, what services are most helpful, how trauma is addressed in services, and how services could be improved for this vulnerable population of women